Literature review and case report: Current concepts for concomitant intra and extracapsular fractures of neck of femur in elderly patients. (April 2017) - Saleeb, H; Kanvinde, R; Rahman, T
Abstract: Though the incidence of concomitant ipsilateral intracapsular and extracapsular fracture neck of femur is still a rare presentation in day to day fracture hip admissions. Cases of simultaneous ipsilateral intra- and extra-capsular neck of femur fractures are forestalled with problems relating to diagnosing this injury as well as debate regarding optimal methods of fixation versus arthroplasty. We did a literature review to assess frequency of such fracture incidence, highlight methods of treatment applied, current practice for management as well as case report presentation.